Prevalencia de helmintos enteroparásitos zoonóticos y factores asociados en caninos domésticos (canis familiaris) en el barrio tandacato de la parroquia San Juan de Pastocalle. - Bedoya Brito, Daniel Alejandro (2018)
The gastrointestinal parasites speciallyhelminthes are the causers of parasites illnesses in domestics canines, whereby the present research was develop with the purpose of determine the prevalence of helminthes zoonotic enteroparasites and associated factors in domestics canines (canis familiaris)through coproparasitictests inTandacato neighborhood of San Juan de Pastocalle parish. The researchwas conducted in 75 domestic canines (canis familiaris) from Tandacato neighborhood, where it was applied a survey to the owners of dogs aboutassociated factors in wherethe canines are unwrapped, also the use of a clinic index card in in the research units. It was developed coproparasitic tests to stablish the presence of gastrointestinal parasites, getting in that way the following results: 81% of the 75 samples of canine stools were positive to parasitic forms of gastrointestinal helminthes as: ancylostoma (43%), uncinaria (29%) and toxocara (25%).The surveys to determine associated factors show that 85% of canines have large spaces and the other 15% space is reduced; the type of canines feeding that in 77% was home-cooked food and 13% is home-made food and pellets; about the frequency offeces cleaning of canines is about 75%; the frequency of deworming where 73% of canines were not dewormed and 97% had never had veterinary checkings. After the research the results were socialized showing that the associated factors determine the presence of helminths and enteroparasites. The social impact is interpreted as the pet’s responsible possession in order to prevent parasites zoonotic parasitic diseases and animal wellness